Attentional ability among survivors of leukaemia. Issue 4 (1st April 1999) - Rodgers, J; Horrocks, J; Britton, P G; Kernahan, J
Abstract : Attentional ability in 19 survivors of acute lymphoblastic leukaemia and 19 sibling controls was assessed using a neuropsychological model of attention. Analysis revealed that children who had received treatment for leukaemia exhibited significantly poorer performance on measures of the "focus encode" and "focus execute" elements of attention and on measures of the ability to respond to external cues and feedback. No significant differences in performance were found for measures of sustained attention and the ability to shift attention. These results indicate that children who have received treatment for leukaemia may experience highly specific attentional deficits that could have an impact on academic performance, particularly mathematical and reading skills. It is suggested that this underlying attentional deficit might be the source of the neuropsychological sequelae associated with the disease. Future attempts at remediation should incorporate activities specifically designed to ameliorate focusing difficulties.